Pan-TGFβ inhibition by SAR439459 relieves immunosuppression and improves antitumor efficacy of PD-1 blockade. (1st January 2020) - Greco, Rita; Qu, Hongjing; Qu, Hui; Theilhaber, Joachim; Shapiro, Gary; Gregory, Richard; Winter, Christopher; Malkova, Natalia; Sun, Frank; Jaworski, Julie; Best, Annie; Pao, Lily; et al.
ABSTRACT: TGFβ is a pleiotropic cytokine that may have both tumor inhibiting and tumor promoting properties, depending on tissue and cellular context. Emerging data support a role for TGFβ in suppression of antitumor immunity. Here we show that SAR439459, a pan-TGFβ neutralizing antibody, inhibits all active isoforms of human and murine TGFβ, blocks TGFβ-mediated pSMAD signaling, and TGFβ-mediated suppression of T cells and NK cells. In vitro, SAR439459 synergized with anti-PD1 to enhance T cell responsiveness. In syngeneic tumor models, SAR439459 treatment impaired tumor growth, while the combination of SAR439459 with anti–PD-1 resulted in complete tumor regression and a prolonged antitumor immunity. Mechanistically, we found that TGFβ inhibition with PD-1 blockade augmented intratumoral CD8 + T cell proliferation, reduced exhaustion, evoked proinflammatory cytokines, and promoted tumor-specific CD8 + T cell responses. Together, these data support the hypothesis that TGFβ neutralization using SAR439459 synergizes with PD-1 blockade to promote antitumor immunity and formed the basis for the ongoing clinical investigation of SAR439459 in patients with cancer (NCT03192345).